2010
DOI: 10.1371/journal.pone.0009384
|View full text |Cite
|
Sign up to set email alerts
|

HAMLET Interacts with Lipid Membranes and Perturbs Their Structure and Integrity

Abstract: BackgroundCell membrane interactions rely on lipid bilayer constituents and molecules inserted within the membrane, including specific receptors. HAMLET (human α-lactalbumin made lethal to tumor cells) is a tumoricidal complex of partially unfolded α-lactalbumin (HLA) and oleic acid that is internalized by tumor cells, suggesting that interactions with the phospholipid bilayer and/or specific receptors may be essential for the tumoricidal effect. This study examined whether HAMLET interacts with artificial mem… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
79
0
1

Year Published

2011
2011
2016
2016

Publication Types

Select...
3
2
1

Relationship

0
6

Authors

Journals

citations
Cited by 55 publications
(82 citation statements)
references
References 37 publications
(55 reference statements)
2
79
0
1
Order By: Relevance
“…However, apart from these quite specific effects of HAMLET, there is also evidence of a more crude effect connected to membrane interactions and alterations. -LA binds to the membrane, but HAMLET causes loss of membrane integrity and leakage of lipid membranes [35] and ELOA, the cytotoxic complex between equine lysozyme and OA, has also been shown to induce loss of membrane integrity with ELOA accumulating at the cell membrane until the cells rupture and ELOA fills the cells [11,36].…”
Section: Discussionmentioning
confidence: 99%
“…However, apart from these quite specific effects of HAMLET, there is also evidence of a more crude effect connected to membrane interactions and alterations. -LA binds to the membrane, but HAMLET causes loss of membrane integrity and leakage of lipid membranes [35] and ELOA, the cytotoxic complex between equine lysozyme and OA, has also been shown to induce loss of membrane integrity with ELOA accumulating at the cell membrane until the cells rupture and ELOA fills the cells [11,36].…”
Section: Discussionmentioning
confidence: 99%
“…In addition, it has been observed that -LA is able to rapidly insert itself into the lipid bilayer at pH 2 [75]. However, native human -LA is only inefficiently bound to and internalized by tumor cells, and does not translocate to the nucleus, nor influence tumor cell viability [3,5,68,69,76]. Even partial unfolding of human -LA has been shown to be insufficient for increased protein internalization into tumor cells [38].…”
Section: Cellular Trafficking Of Hamletmentioning
confidence: 99%
“…Even partial unfolding of human -LA has been shown to be insufficient for increased protein internalization into tumor cells [38]. In addition, human -LA and oleic acid alone were unable to alter membrane structures, further indicating the necessity of interaction between unfolded -LA and an associated fatty acid for efficient internalization of the HAMLET complex in tumor cells [76].…”
Section: Cellular Trafficking Of Hamletmentioning
confidence: 99%
See 2 more Smart Citations